Labor Market Strength and Declining Community College Enrollment - Joshua Goodman; Joseph Winkelmann (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Declining U.S. college enrollments over the past 15 years have triggered questions about the health of the postsecondary sector. Using institution-level data, we make four points. First, such declines are driven not by the four-year sector but by two-year community colleges, which have apparently shrunk by over 30% since the peak of the Great Recession. Second, over one-third of this apparent decline is an artifact of some community colleges being reclassified as offering four-year degrees. Third, pre-Great Recession data shows a 1 percentage point increase in the local unemployment rate increases first-time community college enrollment by 2 percent, suggesting many students are on the margin between community college and job opportunities. For-profit college enrollments are similarly countercyclical, while public and private four-year college enrollments appear acyclical. Our estimates suggest that strengthening labor markets explain about 60% of the post-Great Recession decline in first-time community college enrollment. Fourth, students whose enrollment decisions are most sensitive to labor market conditions appear unlikely to have completed a degree. Though declining community college enrollments are a challenge for postsecondary institutions, it is less clear whether they signal a problem for students on the margin of enrollment.
Keywords: I23; J24; 330; community college; labor market conditions; unemployment rate